2021
DOI: 10.11606/s1518-8787.2021055003125
|View full text |Cite
|
Sign up to set email alerts
|

Efetividade do GeneXpert® no diagnóstico da tuberculose em pessoas que vivem com HIV/aids

Abstract: OBJETIVO Identificar e sintetizar o conhecimento científico produzido a respeito da efetividade do teste GeneXpert no diagnóstico da tuberculose (TB) pulmonar em pessoas vivendo com HIV/aids. MÉTODOS Revisão integrativa da literatura, cuja busca foi feita nas plataformas Embase, Scopus, PubMed, Cinahl, Academic Search Premier, Socindex e Lilacs, em dezembro de 2019. Os estudos levantados passaram por duas etapas de seleção: leitura dos títulos e resumos por dois revisores de forma independente, utilizando a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…In the era of whole-genome sequencing, exploring genome data from clinical isolates is useful to generate datasheets of putative antibiotic resistance polymorphisms. In this same context, PCR-based commercial systems to detect these polymorphisms are widely available for M. tuberculosis ( 30 32 ), although their introduction into nontuberculous mycobacteria is far from optimal. However, these genomic methods have previously required establishing a direct link between chromosomal polymorphisms and antimicrobial resistance, and this has been otherwise the result of long-term observation and characterization of clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of whole-genome sequencing, exploring genome data from clinical isolates is useful to generate datasheets of putative antibiotic resistance polymorphisms. In this same context, PCR-based commercial systems to detect these polymorphisms are widely available for M. tuberculosis ( 30 32 ), although their introduction into nontuberculous mycobacteria is far from optimal. However, these genomic methods have previously required establishing a direct link between chromosomal polymorphisms and antimicrobial resistance, and this has been otherwise the result of long-term observation and characterization of clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In countries with low endemicity rates, the sensitivity and the specificity of Xpert MTB/RIF vary between 82, 95, and 98% for sensitivity and 96 and 99% for specificity. However, in countries with high endemicity, these rates vary between 80 and 88% for sensitivity and between 95 and 98% for specificity [26][27][28].In another study, Faria et al [29] reported Xpert MTB/RIF assay's sensitivity ranging from 68% to 100%. Specificity ranged from 91.7% to 100%, the positive predictive value from 79.2% to 96.1%, and the negative predictive value from 84.6% to 99.3%.…”
Section: Discussionmentioning
confidence: 99%
“…However, in countries with high endemicity, these rates vary between 80% and 88% for sensitivity and between 95 and 98% for specificity [30][31][32]. In another study, Faria et al [33] reported that the sensitivity of the GeneXpert MTB/RIF assay ranges from 68% to 100%. Specificity ranged from 91.7% to 100%, the positive predictive value from 79.2% to 96.1%, and the negative predictive value from 84.6% to 99.3%.…”
Section: Discussionmentioning
confidence: 99%